DIAgnosis and Management Of familial hypercholesterolemia in a Nationwide Design (DIAMOND-FH): Prevalence in Switzerland, clinical characteristics and the diagnostic value of clinical scores. (October 2018) - Miserez, A.R.; Martin, F.J.; Spirk, D.
Abstract: Background and aims: In Switzerland, the prevalence of familial hypercholesterolemia (FH) due to pathogenic apolipoprotein B-100 gene ( APOB ) variants was known, but not the prevalence of FH due to pathogenic low-density lipoprotein-receptor gene ( LDLR ) variants. Phenotypic differences ( LDLR versus APOB ) might affect the diagnostic value of the Dutch Lipid Clinic Network (DLCN) score and Simon Broome Diagnostic Criteria (SBDC). Methods: A total of 2734 Swiss subjects were investigated, 2221 unselected subjects from three representative population surveys for estimation of the prevalence ( LDLR variants), and 513 subjects from the DIAgnosis and Management Of familial hypercholesterolemia in a Nationwide Design (DIAMOND-FH) study for comparisons of phenotypic characteristics ( LDLR versus APOB variants), diagnostic values of clinical scores, and cardiovascular outcome. Results: In 7 of 2221 individuals, FH ( LDLR ) was diagnosed (prevalence of FH due to LDLR variants: 1/317, prevalence of FH due to both LDLR and APOB variants: 1/125 to 1/135). In FH ( APOB ) patients under 35 years of age, mean total cholesterol (TC) was <8.5 mmoL/L but increased above 35. In FH ( LDLR ), TC was >8.5 mmoL/L in all age groups. This difference was crucial for the diagnosis of FH and resulted in a significantly lower sensitivity of clinical scores in FH ( APOB ) (DLCN: 13.8%, p < 0.0001; SBDC: 22.5%, p = 0.005). Thus, both scores were not useful for the definite diagnosis of FH due to APOB variants. Regarding the cardiovascular outcome, no differences ( LDLR versus APOB ) were found above 60 years. In countries with high percentages of FH due to APOB variants, cascade screening and molecular testing appear to be much more cost-effective. Highlights: Prevalence estimation of familial hypercholesterolemia (FH) due to pathogenic LDLR and APOB variants in Switzerland. Comparison of phenotypic characteristics of FH due to pathogenic LDLR and APOB variants in Switzerland. Comparison of the diagnostic value of clinical scores in FH due to pathogenic LDLR and APOB variants. Comparison of premature atherosclerosis and the onset of cardiovascular complications in FH due to LDLR versus APOB variants.